Strategi Pengembangan e-Government di Dinas Komunikasi dan Informatika Kota Tanjungpinang - Nafisah Aulia Rani; Rumzi Samin; Okparizan (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2023)
Since 2018 the Tanjungpinang City Government has started developing e-Government. e-Government development efforts are also a target in the 2018-2023 RPJMD of Tanjungpinang City in 2022 with the coordinator are Dinas Communication and Information of Tanjungpinang City . The purpose of this study is to find out how the strategy carried out by the Dinas Communication and Informatics in developing e-Government in the city of Tanjungpinang. The method used in this study was a qualitative descriptive method with 5 informants and data collection techniques and tools in the form of observation, interviews, and documentation with the research locus is Dinas Communication and Informatics Tanjungpinang City. The results of this study using the ITPOSMO theory from Hungger and Whalen are, (1) Information, The state of the Information owned by Diskominfo is by having the official website of the Tanjungpinang city government and SIPA Kominfo, (2) Technology, The state of the technology that exists at Dikominfo is a lack of network capacity, (3) Processes, As for the process carried out in the development of e-Government by providing network capacity and SIPA Kominfo, (4) Objective and Value, the situation to be achieved is the integrity of public services and employment archive, but for now what has started to have integrity is only the employment archive application (5) Staff and Skills. The condition of the staff and also the skills possessed by the Ministry of Communication and Informatics is that they still have incompetent human resources in the ICT field (6) Management and Structure, with the presence of Mayor Number 8 of 2022 and the existence of applications staffing formed by Pemko who are able to provide assistance in carrying out e-Government development in the city of Tanjungpinang (7) Others, the most influential resources are funds and time, Diskominfo is still experiencing a lack of funds due to post-Covid-19 economic recovery which causes all E-Government development efforts are hampered. The conclusion of this study is that the Tanjungpinang City Communications and Informatics Office in developing e-Government does not yet have its own innovative strategy due to unexpected obstacles such as Covid-19.